PRINCIPAL GAINS AND PHASES - INSENSITIVE ROBUSTNESS MEASURES FOR ASSESSING THE CLOSED-LOOP STABILITY PROPERTY - Kouvaritakis, B; Postlethwaite, I (1982)
The use of principal gains and phases in assessing the robustness of the closed-loop stability property is examined. An improved version of the recently developed principal gain-phase method is presented, and conditions are derived under which the technique is insensitive to small perturbations.